Effect of cyclic freeze–thaw treatments on the dynamic fracture characteristics of granite: Laboratory testing. (December 2022) - Liu, Chuanju; Zhang, Qianjun; Zhu, Qiang; Deng, Hongwei
Highlights: The porosity of rock samples increases with the number of freeze–thaw cycles, while static and dynamic fracture toughness decreases, indicating that freeze–thaw cycles degrade the microstructure and adversely affect the mechanical properties. The fractal dimensions increased with the freeze–thaw cycles increased. The freeze–thaw effect increases the roughness of fracture surface, which corresponds to the decrease of fracture toughness. The dynamic fracture toughness increases with the increase of loading rate. This indicates that the freeze–thaw rock under high dynamic load has greater fracture resistance than that under slow dynamic load. Abstract: In this study, the dynamic fracture toughness of freeze-thawed granite was studied. Different freeze–thaw (F-T) cycles were used to treat notched semicircular bending (NSCB) granite samples. The microstructure changes of samples treated with different numbers of F-T cycles were measured by a nuclear magnetic resonance (NMR) testing system. The dynamic fracture toughness was obtained by dynamic testing with split Hopkinson pressure bar (SHPB) equipment. In addition, the roughness of the rock fracture surface was studied using fractal geometry, and the F-T damage was defined using fractal dimensions. On this basis, a dynamic fracture toughness prediction model is proposed. The influence of the F-T cycle and loading rate on fracture toughness are discussed.